Infiltration of Mast Cells in Scalp Biopsies of Patients with Alopecia Areata or Androgenic Alopecia Versus Healthy Individuals: A Case-Control Study: - Nasiri, Soheila; Salehi, Alireza; Rakhshan, Azadeh (Galen Medical Journal, 2020)
Background: Alopecia areata (AA) and androgenic alopecia (AGA) are the most common types of alopecias. Recently, the role of mast cells in inflammatory diseases has become the focus of many studies. However, few studies have been conducted on their role in AA and AGA. Therefore, our study aimed to quantitatively evaluate the presence of mast cells in the AA and AGA specimens.Materials and Methods: Three groups of AA, AGA, and healthy control were studied (each group with 20 subjects). Patients were randomly selected from those referred to the dermatology clinics of Shahid Beheshti University. Specimens were obtained from the scalp, and perifollicular and perivascular areas were investigated. Results: Significantly higher perifollicular and perivascular mast cell counts were seen in both AGA and AA groups compared to healthy control (P<0.001 for both). Moreover, AA patients had more frequent perivascular mast cells than the AGA group (P=0.042). Among patients aged <40 years, perifollicular and perivascular mast cell counts were not significantly different among the three groups; however, subjects over 40 years of age in both groups had significantly more perifollicular and perivascular mast cells than healthy participants. There was a significant positive correlation between disease severity and mast cell counts in both perifollicular and perivascular areas in AA patients (P=0.001 for both). Conclusion: There was a significantly increased infiltration of mast cells in AA and AGA patients, and this increase was age and severity dependent. Moreover, the increase in mast cell proliferation is more dominant in AA patients. [GMJ.2020;9:e1962]